2020
DOI: 10.3390/v12080810
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Epigenetic Regulation of Endogenous Retroviruses: The Role of Trans-Acting Modifiers

Abstract: Approximately 10 percent of the mouse genome consists of endogenous retroviruses (ERVs), relics of ancient retroviral infections that are classified based on their relatedness to exogenous retroviral genera. Because of the ability of ERVs to retrotranspose, as well as their cis-acting regulatory potential due to functional elements located within the elements, mammalian ERVs are generally subject to epigenetic silencing by DNA methylation and repressive histone modifications. The mobilisation and expansion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…Our work is consistent with previous research on strain-specific modifiers ( 35 ). A growing number of ERV-derived mouse mutations whose phenotypic penetrance is dependent on genetic background have been associated with modifier genes located in an interval on Chr13-cl.…”
Section: Discussionsupporting
confidence: 93%
“…Our work is consistent with previous research on strain-specific modifiers ( 35 ). A growing number of ERV-derived mouse mutations whose phenotypic penetrance is dependent on genetic background have been associated with modifier genes located in an interval on Chr13-cl.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, while the other studies outlined above largely have not pinpointed causal factors, the overlapping molecular and physiological QTL harbor clusters of newly emergent murine KZFPs (Kauzlaric et al , 2017; Bruno et al , 2019). This provides exciting future work into assigning causality to a rapidly evolving gene family whose divergence in different strain backgrounds may account for evolution of regulatory function that shapes development and disease (Elmer & Ferguson‐Smith, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in some cases IAP methylation is modulated by genetic background ( Bertozzi et al, 2020 ; Elmer and Ferguson-Smith, 2020 ; Rakyan et al, 2003 ; Wolff, 1971 ). To assess whether this is the case for Iap5-1 methylation, we carried out reciprocal crosses between B6 and wild-derived CAST/EiJ (CAST) mice (BC, B6 female × CAST male; CB, CAST female × B6 male).…”
Section: Resultsmentioning
confidence: 99%